INTERACTION BETWEEN A CHROMOSOME 10 RET ENHANCER AND CHROMOSOME 21 IN THE DOWN SYNDROME-HIRSCHSPRUNG DISEASE ASSOCIATION - Arnold, Stacey (2009)
Individuals with Down syndrome (DS) display a 40-fold greater risk of Hirschsprung disease (HSCR) than the general population of newborns implicating chromosome 21 in HSCR etiology. Here we demonstrate that the RET enhancer polymorphism RET+9.7 (rs2435357:C>T) at chromosome 10q11.2 is associated with HSCR in DS individuals both by transmission disequilibrium (P=0.0015) and case-control (P=0.0115) analysis of matched cases. Interestingly, the RET+9.7 T allele frequency is significantly different between individuals with DS alone (0.26±0.04), HSCR alone (0.61±0.04), and those with HSCR and DS (0.41±0.04), demonstrating an association and interaction between RET and chromosome 21 gene dosage. This is the first report of a genetic interaction between a common functional variant (rs2435357) and a not infrequent copy number error (chromosome 21 dosage) in two human developmental disorders.